2004
DOI: 10.1158/1078-0432.ccr-04-0659
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Acyclic Retinoid and OSI-461 on Growth Inhibition and Gene Expression in Human Hepatoma Cells

Abstract: Hepatoma is one of the most frequently occurring cancers worldwide. However, effective chemotherapeutic agents for this disease have not been developed. Acyclic retinoid, a novel synthetic retinoid, can reduce the incidence of postsurgical recurrence of hepatoma and improve the survival rate. OSI-461, a potent derivative of exisulind, can increase intracellular levels of cyclic GMP, which leads to activation of protein kinase G and induction of apoptosis in cancer cells. In the present study, we examined the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 42 publications
2
55
0
Order By: Relevance
“…ACR suppresses the growth of HCC cells by inhibiting RXRa phosphorylation and restoring its original function as a master regulator of nuclear receptors (15,(22)(23)(24). Therefore, the expression levels of the RARb, p21 CIP1 , cyclin D1, c-Fos, and c-Jun genes, which are ACR targets (12)(13)(14)(15)28), were notably regulated by treatment with this agent. Among these molecules, RARb seems to be the most important with respect to the induction of apoptosis (36).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…ACR suppresses the growth of HCC cells by inhibiting RXRa phosphorylation and restoring its original function as a master regulator of nuclear receptors (15,(22)(23)(24). Therefore, the expression levels of the RARb, p21 CIP1 , cyclin D1, c-Fos, and c-Jun genes, which are ACR targets (12)(13)(14)(15)28), were notably regulated by treatment with this agent. Among these molecules, RARb seems to be the most important with respect to the induction of apoptosis (36).…”
Section: Discussionmentioning
confidence: 98%
“…Effects of ACR on the expression levels of RARb, p21 CIP1 , cyclin D1, c-Fos, and c-Jun mRNA in the livers of DEN-treated db/db mice ACR inhibits the growth of HCC cells by increasing the cellular levels of RARb and p21 CIP1 but decreasing the levels of cyclin D1, and these effects might be associated with the restoration of RXRa function (12)(13)(14)(15). It also suppresses the growth of cancer cells by inhibiting the activity of AP-1, which comprises the Jun and Fos oncoprotein families (28).…”
Section: General Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…OSI-461 exhibits a high affinity for PDE 2 and 5 compared to other drugs in this class thus resulting in greater selectivity for tumor cells [37]. Preclinical studies using OSI-461 have shown antitumor activity against a broad range of both solid and hematologic human cancer cell lines as both a single agent and in combination with other potential anticancer therapies [19,28,29,37,41]. This phase I and pharmacologic study was designed to evaluate the safety and toxicology profile of OSI-461 as well as determine the effect of food on the PKs of OSI-461 in patients with advanced malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In SW480 colon cancer cells lines at doses twice that of the IC50, OSI-461 was able to induce M phase cell cycle arrest independent of PKG activation resulting in depolymerization of microtubules, inhibition of spindle formation and induction of multinucleated cells [43]. In addition, modulation of key mechanisms involved in the malignant transformation has been seen in with single-agent use in LNCaP prostate cells and in combination with acyclic retinoid in HepG2 hepatoma cells [18,29].…”
Section: Introductionmentioning
confidence: 99%